Is universal antifungal prophylaxis mandatory in adults after lung transplantation? A review and meta‐analysis of observational studies. Issue 12 (25th October 2016) - Pilarczyk, Kevin; Haake, Nils; Heckmann, Jens; Carstens, Henning; Haneya, Assad; Cremer, Jochen; Jakob, Heinz; Pizanis, Nikolaus; Kamler, Markus
Abstract: Background: Lung transplant (LTX) recipients are at high risk of invasive Aspergillus infections (IAI). However, no randomized‐controlled trials (RCT) or international guidelines on antifungal prophylaxis (AFP) in the LTX population exist. Methods: A meta‐analysis was performed to determine whether AFP reduces the rate of IAI after LTX. A total of six eligible observational studies (five with no prophylaxis, one with targeted prophylaxis, three studies including heart/lung transplantation) with a total of 748 patients were included. Results: The pooled odds ratio (OR) for IAI (62 IFI in the intervention arm and 82 in the control group) was 0.234 (95% confidence interval [CI] 0.097‐0.564, P =0.001, z =−3.237). Pooled studies were characterized by substantial heterogeneity ( I 2 =66.64%); number needed to treat was 6.8. A subgroup analyses with exclusion of heart transplant recipients also showed a statistically significant reduction in IAI with AFP (OR 0.183, 95% CI 0.0449‐0.744, P =0.018). Conclusion: This study suggests that universal antifungal prophylaxes reduces incidence of IAI after LTX. However, included studies are limited by small sample size, single‐center structure without randomization, mixed population (including heart/heart‐lung transplant), and heterogeneity due to variations in immunosuppression, type, and duration of AFP. Therefore, there is a clear need for an adequately powered RCT.